2021
DOI: 10.3390/jof7070541
|View full text |Cite
|
Sign up to set email alerts
|

Recent Findings in Azaphilone Pigments

Abstract: Filamentous fungi are known to biosynthesize an extraordinary range of azaphilones pigments with structural diversity and advantages over vegetal-derived colored natural products such agile and simple cultivation in the lab, acceptance of low-cost substrates, speed yield improvement, and ease of downstream processing. Modern genetic engineering allows industrial production, providing pigments with higher thermostability, water-solubility, and promising bioactivities combined with ecological functions. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 116 publications
0
17
0
Order By: Relevance
“…The pigments produced in Pigment Complex A were first analyzed by UV/Vis diode array chromatography. Using the same chromatographic conditions, we proceeded to the determination of these compounds using HR-MS. For the identification of the compounds, we searched the current literature for the known metabolites of Penicillium purpurogenum [ 18 , 19 , 20 ], collected all the reported compounds and created an in-house library containing their chemical structures. We used this library in conjunction with Bruker’s MetaboBASE Plant Library to annotate the compounds being reported in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…The pigments produced in Pigment Complex A were first analyzed by UV/Vis diode array chromatography. Using the same chromatographic conditions, we proceeded to the determination of these compounds using HR-MS. For the identification of the compounds, we searched the current literature for the known metabolites of Penicillium purpurogenum [ 18 , 19 , 20 ], collected all the reported compounds and created an in-house library containing their chemical structures. We used this library in conjunction with Bruker’s MetaboBASE Plant Library to annotate the compounds being reported in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…Tartrazine reduction produces sulfanilic acid and aminopyrazolone, both of which can cause tissue injury via reactive oxygen species (ROS) generation [11] . Tartrazine is reported to be one of the most arguable coloring agents [12] . It was reported that it can exacerbate liver toxicity as it contains the hepatotoxic butylated hydroxytoluene (BHT), causing hepatic centrilobular necrosis, hemorrhagic death, and elevated serum transaminase activities after 24 hours of administration [13] .…”
Section: Pharmacology and Forensic Medicinementioning
confidence: 99%
“…By 2024, it was expected that the world color market used in food industry will reach approximately 5.7 billion US dollar 6 . Unfortunately, the basic science and industry still have not overcome the high cost and low availability of natural pigments 7 . Therefore, the demand for the naturally produced biopigments will continue to rise.…”
Section: Introductionmentioning
confidence: 99%